Caffeine, Alcohol and Tobacco Pattern Use and Risk Factors in Use Risk During Pregnancy in the Middle Zone of Northeastern Thailand (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Prenatal substance use is a public health problem deserving the highest priority of attentionbecause it poses devastating risks of maternal and fetal consequences. Situational analysis of currentsubstance use in pregnancy and its risk factors is essential for effective preventive strategies for maternal andchild health. This study explored the prevalence of risky substance use (caffeine, alcohol, and tobacco) alongwith associated factors patterning among pregnant women in the middle zone of Northeastern Thailand.Method: This cross--sectional study was conducted in 58 district hospitals located in the middle zone ofnortheastern Thailand. The participants were 944 pregnant women attending antenatal clinics chosen basedon consecutive sampling. Data collection used a questionnaire, and data analysis used multiple logisticregression.Result: More than two-thirds of the pregnant women (70.1%) reported current substance use, includingcaffeine (61.6%), alcohol (20.7%), and tobacco (3.3%). Risk factors such as family caffeine use (AOR=2.83,95%CI: 2.02-3.97) and couple relationship (AOR=1.58, 95%CI: 1.07-2.33) were found to be associated withcaffeine in use risk, while marital status (AOR=2.53, 95%CI: 1.11-5.77), couple relationship (AOR=2.27,95%CI: 1.05-4.91), and family alcohol use (AOR=3.54, 95%CI: 1.49-8.42) were those associated withalcohol in use risk. It was notable that while family tobacco use (AOR=3.85, 95%CI: 1.05-14.06) wasassociated with tobacco in use risk, age was found to be its protective factor (AOR=0.31, 95%CI: 0.10-0.95)among those in the tobacco use risk group.Conclusion: Currently there is strong evidence about the risky substance use during pregnancy. Modificationsolutions for suitable consumption behavior should targeted pregnant women with family substance use,poor couple relationships, single status and more than 20 years, old.